Quantifying mass balance of East-Karakoram glaciers using geodetic technique - Kumar, Anant; Negi, H.S.; Kumar, Kamal; Shekhar, Chander; Kanda, Neha (Polar Science, 2019)
The Karakoram Range comprises the heavily glaciated mountains outside the Polar regions. A comprehensive assessment of glaciers variation in this region is crucial to ascertain constant water supply under different scenarios of futuristic climate change. Lack of accessibility to the Karakoram region has limited the use of conventional methods in monitoring variations in thickness and mass of glaciers, alternatively promoting the use of remote sensing based methods. The present study quantifies changes in thickness and mass budget of 24 glaciers in East-Karakoram region using geodetic technique. The Digital Elevation Model (DEM) adjustments and comparisons were made between Shuttle Radar Topography Mission (SRTM) C-band DEM, year 2000 and recent DEMs of the years 2009 and 2014, which were generated using stereo pairs of Panchromatic Remote Sensing Instrument for Stereo Mapping (PRISM) onboard the Advanced Land Observing Satellite (ALOS) and Cartosat-1 respectively. The vertical accuracy of recent DEMs was assessed using ICESat-1 laser points. Other biases such as elevation dependent, radar penetration, terrain curvature and seasonality were also rectified before computing the glacier mass balance. Geodetic esimates indicate an overall marginal thinning (−0.09 ± 0.16 m/yr) and negative mass budget (−0.08 ± 0.13 m.w.e./yr) during the years 2000–2014. Interestingly, one glacier showed surge-type activity (advancing and thickening terminus) during 2000-2014, with highest (0.59) Accumulation Area Ratio (AAR) amongst studied glaciers. Time series analysis of climate data (temperature and precipitation) recorded at field observatories depict overall warming in the East-Karakoram region. The higher rate of mass loss during 2009–2014 (−0.07 ± 0.13 m.w.e./yr) compared to 2000–2009 (−0.05 ± 0.12 m.w.e./yr) was found in agreement with the rise in temperature and decline in precipitation over the region during different years. The results thus indicate an insignificant mass loss in East-Karakoram glaciers and thus exhibit a ...